The impact of educational level toward leadership among UiTM student / Muhammad Afiq Nor Khairull-Amli - Nor Khairull-Amli, Muhammad Afiq (2019)
This project involves discovering how educational level might impact the leadership among UiTM student based on Islamic perspective. The goal is to show that how educational level might give an impact towards leadership among UiTM student based on Islamic perspective. This has been done by examining events such as the involvement of students itself, the social life management and also the perception and influence of people towards leadership. The target population is among the students in UiTM Shah Alam who currently involve in leadership experience and tenure like Majlis Perwakilan Pelajar, Jawatankuasa Perwakilan Kolej, Sekitariat Mahasiswa Fakulti, clubs and Uniform Units. The objectives of this research are to examine whether there is a relationship between involvement of students, social life management and perception towards leadership focusing on Islamic perspectives and do it relate or give an impact by educational level and which one of the factor are most give an impact by educational level. Upon examination of these research, it becomes clear that there is a positive result showing that there is an impact from educational level towards leadership. The conclusion of the research is the educational level does give an impact especially in leadership that refers to an Islamic concept and scope of perspectives.